2012
DOI: 10.1039/c2np00066k
|View full text |Cite
|
Sign up to set email alerts
|

Largazole: From discovery to broad-spectrum therapy

Abstract: The cyclic depsipeptide largazole from a cyanobacterium of the genus Symploca is a marine natural product with novel chemical scaffold and potently inhibits class I histone deacetylases (HDACs). Largazole possesses highly differential growth-inhibitory activity, preferentially targeting transformed over non-transformed cells. The intriguing structure and biological activity of largazole have attracted strong interest from the synthetic chemistry community to establish synthetic routes to largazole and to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
158
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(162 citation statements)
references
References 44 publications
(116 reference statements)
2
158
0
1
Order By: Relevance
“…2,3 Because of its potency, class I selectivity, and in vivo efficacy, 4 largazole ( 1 ) possesses great potential as an anti-cancer agent. 5 Additionally, largazole ( 1 ) has shown a variety of other biological activities, such as the in vitro and in vivo induction of osteoblast differentiation biomarkers, 6 the sensitization of EBV+ tumor cells to the anti-herpes drug ganciclovir (GCV), 7 the inhibition of ubiquitin activating enzyme, E1, 8 and the in vitro and in vivo induction of apoptosis in hepatic stellate cells (HSC) in liver fibrosis models. 9 These promising biological activities led to 11 total syntheses 2,3,1018 and a wide variety of analogues of largazole ( 1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Because of its potency, class I selectivity, and in vivo efficacy, 4 largazole ( 1 ) possesses great potential as an anti-cancer agent. 5 Additionally, largazole ( 1 ) has shown a variety of other biological activities, such as the in vitro and in vivo induction of osteoblast differentiation biomarkers, 6 the sensitization of EBV+ tumor cells to the anti-herpes drug ganciclovir (GCV), 7 the inhibition of ubiquitin activating enzyme, E1, 8 and the in vitro and in vivo induction of apoptosis in hepatic stellate cells (HSC) in liver fibrosis models. 9 These promising biological activities led to 11 total syntheses 2,3,1018 and a wide variety of analogues of largazole ( 1 ).…”
mentioning
confidence: 99%
“…28 It is believed that the interactions between this hydrophobic cap region and the macrocycle of largazole ( 1 ) influence its class selectivity. 5,29 However, changes in the thiazole-thiazoline unit of largazole ( 1 ) have not resulted in any significant improvement in its potency or isoform selectivity. 18,2123,26 …”
mentioning
confidence: 99%
“…73 Others such as Luesch have carried out the aldol reaction with acrolein to give the simpler product 46. 75 The vinyl compound is incorporated into the macrocycle, and the thiol sidechain later introduced by alkene cross-metathesis. This approach has the advantage that a variety of zinc binding groups or chain lengths can be appended at a late stage for SAR studies, and confirmed that the natural products contain the optimal chain length for HDAC inhibition.…”
Section: The Depsipeptide Natural Products With a Thiol Warheadmentioning
confidence: 99%
“…Largazole (Hong and Luesch, 2012) was isolated from a marine cyanobacterium of the genus Symploca. This depsipeptide contains a 4-methylthiazoline fused to a thiazole ring and an octanoic thioester side chain, and is another novel chemical scaffold that may preferentially target cancer cells over normal cells; consequently, largazole is a potentially valuable cancer chemotherapeutic.…”
Section: Ribosomal-and Nonribosomal-derived Peptides: a Virtually Unlmentioning
confidence: 99%